Effect of Binding Agent Removal on Aggregation of Lou Soil Nanoparticles - YAN Yuyang; ZHANG Xinran; TANG Yao; HU Feinan; GENG Zengchao; XU Chenyang (Shuitu Baochi Xuebao, 2024)
[Objective] To investigate the effect of binding agent on the aggregation of soil colloidal particles and to clarify the microscopic mechanism of the formation of soil aggregate structures. [Methods] Soil nanoparticles (NP) were obtained from Lou soil, namely NPs from original Lou soil (NP-Lou), NPs from organic carbon-removed soil (NP-OCR), and NPs from inorganic carbon-removed soil (NP-ICR). The aggregation kinetics, critical coagulation concentrations (CCCs) and surface electricity of three kinds of Lou soil nanoparticles in Na+, Ca2+ and La3+ systems were determined by dynamic light scattering. The Hamaker constant and interaction energy of soil nanoparticles were calculated by Derjauin-Landau-Verwey-Overbeek (DLVO) theory. [Results] In the same solution chemistry condition, the aggregation rate of NP-OCR and NP-ICR decreased and the CCCs value increased compared with NP-Lou. The absolute value of zeta potential of NP-OCR and NP-ICR was lower than that of NP-Lou, which resulted in the decrease of electrostatic repulsive potential energy between nanoparticles. The theoretical calculation of DLVO showed that the Hamaker constant of NP-OCR and NP-ICR was also lower than that of NP-Lou. That was, the attractire van der Waals potential energies of soil nanoparticles also decreased after the removal of inorganic carbon and organic carbon. The combined force calculation results showed that the total potential energy of the interaction between soil nanoparticles after removing inorganic carbon or organic carbon was higher than NP-Lou, so the CCC value was larger. The CCCs difference between NP-ICR and NP-Lou was larger than the CCC difference between NP-OCR and NP-Lou, therefore, soil inorganic carbon affected Lou soil NP aggregation more strongly. [Conclusion] Inorganic carbon and organic carbon enhance the attractive potential energy by increasing the Hamaker constant of the interaction between soil particles, which is important for cementing materials to promote the stability of soil aggregates.